Development of Moss Plant Encyclopedia as a Biology Learning Media for Senior High School Students - Firdani, Azizah Nurul; Sulistiyawati, Sulistiyawati (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to develop an encyclopedia containing the diversity of moss plant species in Selarong Cave as a learning medium and to determine the feasibility and practicality of an encyclopedia of moss plants (Bryophyta) as a biology learning medium. Product development research includes Research and Development (R&D) research using the four-D (4D) development model which is limited to the development stage. The encyclopedia that has been developed is then validated with assessment instruments including validation questionnaire sheets and student response questionnaires. Data analysis uses qualitative data analysis techniques which are then converted into quantitative data. The encyclopedia assessment was carried out by 1 material expert, 1 media expert, 1 biology teacher, and 15 class X students of SMA N 1 Pajangan. The results of validity tests by material experts and media experts show validity so that the product is declared feasible. The results of validity tests by teachers and students show validity so that the product is declared practical. The encyclopedia of moss plants (Bryophyta) in the Selarong Cave area was declared suitable and practical to use as a biology learning medium.